Synthesis and Anti-Inflammatory Activities of Some New Substituted Benzocarboxamide Pyrimidine Derivatives Using N-(4-Acetylphenyl)-5-chloro-2-methoxybenzamide as Starting Material - A. Hussain1, Azza; M. Abdulla2, Mohamed; El-Galil E. Amr3, Abd; A. Al-Omar3, Mohamed; F.A. Shalaby1, Ahmed (Asian Journal of Chemistry, 2014)
A series of substituted pyrimidine derivatives (2-6) were prepared from corresponding chalcones, which were prepared from N-(4-acetylphenyl)-5-chloro-2-methoxybenzamide as starting material. The structure assignments of the newly synthesized compounds are based on chemical and spectroscopic evidence. The pharmacological screening showed that many of these compounds have less toxicity and good anti-inflammatory activities.